Infrared, transient thermal, and electrical properties of silver nanowire thin films for transparent heaters and energy‐efficient coatings. Issue 1 (19th September 2016) - Bobinger, Marco; Angeli, Diego; Colasanti, Simone; La Torraca, Paolo; Larcher, Luca; Lugli, Paolo
Abstract : In this study, we investigate the infrared and electrical properties as well as the thermal response of transparent silver nanowire (AgNW) based thin‐film heaters, when subjected to Joule heating. Controlling the number of layers and hence the deposition time, our spray‐coating technique allows to modulate the thermal and electrical properties of the thin films in a precise manner. In addition, this technique enables the fabrication of homogeneous and large‐area heaters, which, in terms of their electro‐optical properties, nicely compare to the performances of state‐of‐the‐art AgNW transparent electrodes. The thermal response and the electrical properties are accurately reproduced by a purposely developed physical model, which shows that the temperature dependence of the AgNW film resistance is lowered by a factor of 2 compared to bulk silver, independently of the number of deposited layers. Compared to uncoated glass, the emissivity decreases by 58% at a coverage rate of 58%. At the same time, the AgNW film can sustain a transparency as high as 81.3%. Therefore, AgNW‐based thin films can be used as a low‐emissivity coating, for e.g., energy‐efficient window glazing applications. Finally, we accurately determine the fragmentation temperature of AgNWs, which sets the ultimate limitation of use for heating applications.